Simulation as a Central Feature of an Elective Course: Does Simulated Bedside Care Impact Learning? - Michael C. Thomas; Peter J. Hughes (MDPI AG, 2018)
A three-credit, simulation-based, emergency medicine elective course was designed and offered to doctor of pharmacy students for two years. The primary objective was to determine if there was a difference in exam performance stratified by student simulation experience, namely either as an active observer or as part of bedside clinical care. The secondary objective was to report student satisfaction. Examination performance for simulation-based questions was compared based on the student role (evaluator versus clinical) using the Student’s t-test. Summary responses from Likert scale-based student satisfaction responses were collected. A total of 24 students took the course: 12 in each offering. Performance was similar whether the student was assigned to the evaluation team or the clinical team for all of the comparisons (mid-term and final 2015 and 2016, all p-values > 0.05). Students were very satisfied with the course. Of the 19 questions assessing the qualitative aspects of the course, all of the students agreed or strongly agreed to 17 statements, and all of the students were neutral, agreed, or strongly agreed to the remaining two statements. Direct participation and active observation in simulation-based experiences appear to be equally valuable in the learning process, as evidenced by examination performance.